Analisis Penggunaan Metode ACPO (Association of Chief Police Officer) pada Forensik WhatsApp - Prasongko, Riski Yudhi; Yudhana, Anton; Riadi, Imam (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
The development of smartphone technology is increasing, causing cyber crime to increase from year to year. One of the smartphone applications used by criminals is WhatsApp. The WhatsApp application is one of the most widely used insta messaging applications, especially in Indonesia. Violations such as hate speech, defamation, and fraud are common on the WhatsApp social network. This study was conducted with the aim of finding forensic evidence of cyberbullying behavior on the WhatsApp insta messaging application using the Association of Chiefs of Police (ACPO) method. This forensic phase involves planning, arresting, analyzing and presenting to search for digital evidence of cybercrimes using Belkasoft Evidence Center and HashMyFiles software. Digital evidence on smartphones can be found using case scenarios with 13 parameters that have been generated. The results of this study indicate that the Belkasoft Evidence Center digital forensic software is 81.92%, while HashMyfiles can detect the authenticity of digital evidence 79.96%.